1992
DOI: 10.1111/j.1751-1097.1992.tb04261.x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Photoadduct of 4,5',8‐trimethylpsoralen and Adenosine

Abstract: A novel photoadduct of 4,5',8-trimethylpsoralen (TMP) and adenosine was isolated and purified by reverse-phase liquid chromatography. The structure of the photoproduct was determined by various spectral methods and found to be a TMP-adenosine 1:1 adduct resulting from the covalent bond formation between the carbon C(4) of TMP and ribose 4'-carbon of adenosine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…These findings are in direct contrast to a previous study (25) in which PUVA-induced murine skin cancers harbored p53 mutations mainly at 5Ј-TpA sequences (also primary psoralen-binding sites and very likely targets of PUVA-induced mutagenesis) (5,6,(26)(27)(28). Indeed, cell culture studies have shown that in most cases PUVA leads to the formation of thymidine photoadducts or, much less frequently, of cytosine (29) or adenine photoadducts (30). Indeed, (repeated) AT sequences are hotspots for the photochemical reaction of 8-methoxypsoralen (8-MOP) with DNA, whose reactivity seems to increase in the following order: AT K TA ϳ TAT K ATA Ͻ ATAT Ͻ ATATAA (26,31,32).…”
Section: Introductioncontrasting
confidence: 91%
“…These findings are in direct contrast to a previous study (25) in which PUVA-induced murine skin cancers harbored p53 mutations mainly at 5Ј-TpA sequences (also primary psoralen-binding sites and very likely targets of PUVA-induced mutagenesis) (5,6,(26)(27)(28). Indeed, cell culture studies have shown that in most cases PUVA leads to the formation of thymidine photoadducts or, much less frequently, of cytosine (29) or adenine photoadducts (30). Indeed, (repeated) AT sequences are hotspots for the photochemical reaction of 8-methoxypsoralen (8-MOP) with DNA, whose reactivity seems to increase in the following order: AT K TA ϳ TAT K ATA Ͻ ATAT Ͻ ATATAA (26,31,32).…”
Section: Introductioncontrasting
confidence: 91%
“…In another report we described the use of blue light (419 and 447 nm) for the photoactivation of 8-MOP to reduce XL formation to even lower levels (3% and 1%, respectively).' 8 We have also reported the results of different strategies for the targeting of psoralen photoadducts using oligodeoxyribonucleotides to induce the formation o f MA or XL a t a targeted base air.^','^…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to assume that photobiological effects of furocoumarins arise, at least partly, from a [2+2] photocycloaddition involving the 3,4double bond of the pyrone moiety and/or the 4',5'-double bond of the furan moiety of the psoralen on one hand and the 5,6-ethylenic bond of the DNA thymine residue on the other hand. The isolation and the characterization of the 5-MOP adducts to DNA bases have received far less attention as compared to those of 8-MOP and 4,5',8-TMP (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Preliminary photobinding studies showed that, within DNA, the furan-side photoadducts of several bifunctional furocoumarins are the predominant photoproducts whereas in the dry state, the pyrone-side photoadducts are formed preferentially.…”
Section: Introductionmentioning
confidence: 99%